Redline - Sadek, Daniel; Foreman, Robert; Cheng, Andy.; Bjorlin, Nadia; Phillips, Nathan; MacFadyen, Angus, 1963-; Griffin, Eddie, 1968-; Matheson, Tim, 1947-; Johnson, Jesse; Lawton, Denyce; Skylar, Neill; Niven, Barbara; et al. ([New York, N.Y.] : Weinstein Company : Genius Products, 2007)
The idle rich need something unconventional to spend their hard-earned money on. So, they bet on and/or sponsor illegal car races. Unfortunately, one of the drivers, Jason, gets killed trying to impress his Uncle Michael. Michael's philosophies do little to camouflage the fact that he's a psychopathic Mafia don. Carlo is Jason's older brother and a returning Iraqi War hero who goes to an old gun-running buddy and stocks up on military weaponry. Along the way, he rescues Natasha, a would-be pop diva whom Michael is convinced is his cosmically-ordained soul mate. Not to mention, the daughter of a race car champ who suffered a tragic fate, giving her a phobia against racing professionally.
DVD, region 1, widescreen presentation; Dolby Digital.
Closed-captioned.
Title from container.
Nadia Bjorlin, Nathan Phillips, Angus Macfadyen, Eddie Griffin, Tim Matheson, Jesse Johnson, Denyce Lawton, Neill Skylar, Barbara Niven, Marc Crumpton, Hal Ozsan, Faleolo Alailima, Christopher Backus, Kevin Levrone, Todd Lowe.
Director of photography, Bill Butler ; editor, Dallas Puett ; music, Ian Honeyman, Andrew Raiher ; production designer, David L. Snyder ; visual effects supervisor, Jonah Loop, Christopher Francis Woods.
MPAA rating: PG-13; for violence, illegal and reckless behavior, sexual content, language and drug references.
Keywords: Drag racing -- United States -- Drama; Drag racers -- United States -- Drama; Sports sponsorship -- United States -- Drama; Psychopaths -- United States -- Drama; Brothers -- United States -- Drama; Man-woman relationships -- United States -- Drama; Drag racing -- United States -- Drama; Drag racers -- United States -- Drama; Sports sponsorship -- United State -- Drama; Psychopaths -- United States -- Drama; Brothers -- United States -- Drama; Man-woman relationship -- United States -- Drama; Feature films; Adventure films; Video recordings for the hearing impaired; Adventure -- Feature; Feature films; Adventure films